Prospering in Dynamically-Competitive Environments: Organizational Capability as Knowledge Integration - Grant, Robert M. (Organization Science, 1996)
Unstable market conditions caused by innovation and increasing intensity and diversity of competition have resulted in organizational capabilities rather than served markets becoming the primary basis upon which firms establish their long-term strategies. If the strategically most important resource of the firm is knowledge, and if knowledge resides in specialized form among individual organizational members, then the essence of organizational capability is the integration of individuals' specialized knowledge. This paper develops a knowledge-based theory of organizational capability and draws upon research into competitive dynamics, the resource-based view of the firm, organizational capabilities, and organizational learning. Central to the theory is analysis of the mechanisms through which knowledge is integrated within firms in order to create capability. The theory is used to explore firms' potential for establishing competitive advantage in dynamic market settings, including the role of firm networks under conditions of unstable linkages between knowledge inputs and product outputs. The analysis points to the difficulties in creating the “dynamic” and “flexible-response capabilities” which have been deemed critical to success in hypercompetitive markets.